SELF-REPAIR OF INDONESIAN JAPANESE LEARNERS’ SPEAKING: CASE STUDY IN VOCATIONAL TRAINING INSTITUTION - Anisa Arianingsih; Wawan Gunawan; Nuria Haristiani; Dadang Sudana; Ikmal Trianto (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
Self-repair is correcting a sentence's structure or meaning and rewording it to provide more specific information. Exploring the use of self-repair in learners is important as a potential indicator of language attrition in second-language learning. Self-repair can solve misunderstandings and clarify the speaker’s intention. It also allows students to repair their errors without the teacher’s involvement. Previous studies of self-repair in Japanese mostly investigate learners in formal institutions. However, research on using Japanese learners in non-formal institutions is limited. This study investigates the types and the changes in the self-repair of Indonesian Japanese learners’ speaking over a five-month training program in a Vocational Training Institution (LPK). This study used a mixed method, which combined quantitative and qualitative. Participants of this study were 10 Indonesian Japanese learners at an LPK in West Java, Indonesia. The instruments through a monologue speaking task were given at the beginning and end of the training program. The results showed that morphological change is the most frequent self-repair used by learners. However, the least used self-repair at the beginning and end of the training program was different. At the beginning of the training program, the least used self-repair was a phonological change, while at the end, there were phonological and lexical changes. This study showed a tendency for a reduced frequency of self-repair with increased proficiency. This study provided a learning strategy and contributed to developing a curriculum and teaching method that is more effective in improving learners' speaking skills, especially in preparing for work in Japan. However, this study only examines self-repair using monologue speaking tasks with familiar topics. Future studies should investigate self-repair using additional task designs to deepen insights into developmental patterns.